A STUDY OF SEMANTIC, PRAGMATIC AND CULTURAL FEATURES OF "NICE" AND ITS EQUIVALENTS IN VIETNAMESE - Assoc. Prof Dr. Trần Văn Phước (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
- Making an investigation of some semantic, pragmatic, and cultural features of the adjective Nice in English and its equivalents in Vietnamese. - Finding out the features of pragmatics and culture of the adjective Nice. - Raising the individual awareness of the existence of such type of the adjective Nice in the lexicon of each language as well as its positive effect in everyday conversation, especially of some typically linguistic and cultural characteristics.